Comparison of Digital 12‐Lead ECG and Digital 12‐Lead Holter ECG Recordings in Healthy Male Subjects: Results from a Randomized, Double‐Blinded, Placebo‐Controlled Clinical Trial. Issue 6 (28th March 2016) - Wang, Duolao; Bakhai, Ameet; Arezina, Radivoj; Täubel, Jörg
Abstract : Background: Electrocardiogram (ECG) variability is greatly affected by the ECG recording method. This study aims to compare Holter and standard ECG recording methods in terms of central locations and variations of ECG data. Methods: We used the ECG data from a double‐blinded, placebo‐controlled, randomized clinical trial and used a mixed model approach to assess the agreement between two methods in central locations and variations of eight ECG parameters (Heart Rate, PR, QRS, QT, RR, QTcB, QTcF, and QTcI intervals). Results: A total of 34 heathy male subjects with mean age of 25.7 ± 4.78 years were randomized to receive either active drug or placebo. Digital 12‐lead ECG and digital 12‐lead Holter ECG recordings were performed to assess ECG variability. There are no significant differences in least square mean between the Holter and the standard method for all ECG parameters. The total variance is consistently higher for the Holter method than the standard method for all ECG parameters except for QRS. The intraclass correlation coefficient (ICC) values for the Holter method are consistently lower than those for the standard method for all ECG parameters except for QRS, in particular, the ICC for QTcF is reduced from 0.86 for the standard method to 0.67 for the Holter method. Conclusions: This study suggests that Holter ECGs recorded in a controlled environment are not significantly different but more variable than those from the standard method.